'Things of the outside teach me': identity transfer and contextual transformation as expressions of persistent, syncretic cosmology in traditional spiritual and medicinal practice in the south-central Maloti-Drakensberg, southern Africa. Issue 1 (2nd January 2022) - Skinner, Andrew
ABSTRACT: The Maloti-Drakensberg Mountains of southern Africa have a well-established history of contact and hybridity, one that greatly changed the appearances and cultural constitutions of its inhabitant communities. Southern San hunter-gatherers were among those incorporated into a range of new hybridised cultural formats. However, as much as change shows in the art adorning the region's rock shelters, San identity is not routinely expressed among contemporary communities, leaving a question as to how far their ontologies persist into the present. This paper presents results of an interview survey undertaken in southern Lesotho and the adjoining Eastern Cape Province of South Africa. The survey investigated modes of classification employed by traditional medicinal specialists, with particular reference to snakes and rivers, both important motifs across a range of regional idioms. The results are characterised by strongly relational themes and ontological mutabilities that contest conventional presentations of agriculturalist belief systems, despite more apparent community alignment with such identities, while comparing favourably with 'animist' themes in the testimonies of nineteenth-century San informants, including those of Qing in Lesotho and of multiple /Xam individuals from South Africa. These contrasts and similarities are highly suggestive of a syncretic history manifest in the present. They also have potential for representing a continuity of ideology with image-making practice, something that would encourage the inclusion of contextual, contemporary communities in the interpretive process in terms that are decoupled from anthropological expectations regarding those communities' expressed identities.